Efficacy, Safety, and Prognosis of Sequential Therapy with Tamoxifen and Letrozole versus Letrozole Monotherapy for Breast Carcinoma. (14th April 2022) - Lu, Xinli; Qian, Cheng
Abstract : Objective . To explore the efficacy, safety, and patient prognosis of letrozole (LTZ) alone or in sequence with tamoxifen (TAM) for the treatment of breast carcinoma (BC). Methods . In this retrospective study, 150 patients with BC who received treatment in the First People's Hospital of Ningyang County between January 2012 and January 2017 were selected. According to different treatment methods, 99 cases receiving sequential therapy with TAM and LTZ were included in the research group, and the remaining 51 patients receiving LTZ monotherapy were selected as the control group. The efficacy, safety, survival rate, recurrence rate, and blood lipid indices (total cholesterol, TC; triglyceride, TG; high-density lipoprotein cholesterol, HDL-C; and low-density lipoprotein cholesterol, LDL-C) of the two groups were observed and compared. Results . The overall response rate of the research group was statistically higher than that of the control group, and the incidence of adverse reactions was significantly lower. No evident difference was observed in 1-, 3-, or 5-year survival rates between the two groups, while the 3-5-year recurrence rate was obviously lower, and the improvement of blood lipid indices was significantly better in the research group compared with the control group. Conclusion . LTZ alone or in sequence with TAM is effective and safe for the treatment of BC, which can significantly improve the prognosis and blood lipid indices of BC patients.